Human rights and community work. Complementary theories and practices - Ife, Jim; Fiske, Lucy (2006)
Much effort has been placed on developing international understandings of human rights without the corresponding attention to responsibilities. The authors argue that a community development framework may be useful in re-conceiving human rights in a more holistic way, and that social workers and community development workers are well placed to be 'grass roots human rights workers.